Heart rate variability during the first week of an altitude training camp in elite triathletes - Altini, M.; Berk, S.; Janssen, T. W. J. (Sport Performance & Science Reports, 2020)
Training camps at altitude aim at improving performanceby spending time in a hypoxic environment, which typ-ically increases red blood cells and improves oxygen carryingcapacity. Despite these clear pathways, athletes often responddifferently and not always positively (1, 2, 3). Measurementof morning resting heart rate (HR) and heart rate variabil-ity (HRV) can provide a non-invasive assessment of how anathlete is responding to stressors such as altitude. However,little data is available in the context of individual responsesand adaptation to altitude in elite triathletes.